Potential of thermal ablation combined with immunotherapy in peripheral lung tumors: a review and prospect - Yang, Rui; Gu, Chuanjia; Xie, Fangfang; Hong, Siyuan; Herth, Felix; Sun, Jiayuan (Respiration, 2024)
Background: Lung tumors are prevalent malignancies associated with a high mortality rate, imposing significant medical and societal burdens. Although immunotherapy shows promise in improving survival, response rates are relatively modest. Thermal ablation can not only eliminate tumor cells directly but also enhance antitumor immunity response, thus manifesting a remarkable propensity to synergize with immunotherapy. Summary: In this review, we provided a brief overview of the application of thermal ablation in peripheral lung tumors. We summarized the patient selection of thermal ablation. We highlighted the potential of thermal ablation to augment the antitumor immune response, offering a promising avenue for combined therapies. We summarized studies assessing the synergistic effects of thermal ablation and immunotherapy in preclinical and clinical settings. Lastly, we underscored the urgent issues that warrant in-depth exploration when applying thermal ablation and immunotherapy to lung tumor patients. Key Messages: This review emphasized the prospects of using thermal ablation combined with immunotherapy in patients with peripheral lung tumors. However, further research is needed to enhance and optimize this treatment strategy.
Gesehen am 28.10.2024